A atuação do coordenador de curso da licenciatura em matemática na formação inicial do educador matemático - Santos, Renato Augusto dos (2007)
This research report provides for information on the possibilities of performance of the Coordinator of the Course of Licenciature in Mathematics upon the organization and initial formation of the Mathematics educator, course which is connected with a certain socialhistorical context as to processes of idealization, structuring, implementation and transformation of the proposals and of the processes of formation of the course. In order to achieve such object of study, theorical and practical searches have been accomplished upon conceptions present at official documents, upon the literature and speech of the subjects of the research as to the initial formation of the mathematics teacher and as to the performance of the Coordinator of the Course of Licenciature in Mathematics, in this process of formation. During the course of the documental analysis and interviews, concerns on the performance of Course Coordinators have been raised, whether directly or indirectly connected to them; Psychology theoric studies upon the constitution and functioning of the subject and relation between the members of the group of subjects; and the initial formation of the Mathematics teacher. Interviews have been accomplished with professionals from private universities of the Metropolitan Region of São Paulo, who are liable for coordinating academic activities of this kind of course, for such Professionals were concerned on contributing to this research. As a result of the research, it was possible: to identify requirements deemed necessary for the Course Coordinator to perform and, by means of latter s management, obtain results compatible with the objectives drawn for such formation process; to recognize actions, interventions and functions pertinent to the Coordinator of the Course of Mathematics Licenciature as to the organization and functioning of such Course; and to comprehend how the results of the transformation processes of the formative proposals of a course can be benefited with the intervention of such professional